Efficacy of Minimally Invasive Techniques versus Open Surgery for Recurrent Inguinal Hernias: A Meta-Analysis - Ikram Ul Haq; Ali, Babar; Bakkar, Muhammad Abu; Bangash, Rohail Khan; Muhammad, Luqman; Ahmad, Nigar; Hassan, Zohaib; Saeed, Nadia; Nazir, Sumaira (Indus Journal of Bioscience Research, 2024)
Background: Recurrent inguinal hernias present difficult tasks in surgical approaches to address the issue and enhance patient prognosis. Laparoscopic and other forms of obsolete, less invasive surgery are increasingly being preferred to traditional open surgery. Objective: This meta-analysis aims to synthesize the effectiveness of minimal approach strategies compared with the open approach for recurrent inguinal hernia repair. Methods: The present study adhered to the PRISMA flowchart and databases search was conducted in PubMed, Cochrane, Embase, and Scopus. A total of 29 articles were used from the literature published between 2000 and 2024, which compared minimally invasive techniques and open surgery. Meaningfully, assessment parameters drawn from the study were recurrence rates, post-surgery pain, lengths of hospital stay, complications, and, satisfaction. Structural analysis was performed and combined ordinal data were analyzed for comparison of relative effectiveness. Results: It can be seen that, over the different parameters, minimally invasive approaches provided better results. Repeat rate was smaller (6.06% versus 11.14%), early postoperative pain (3.1 versus 5.4 days); shorter hospital stay (2.5 versus 4.8 days). In the following analysis we observed that the complication rate was significantly less in the minimally invasive group (4.2% vs 8.9%) and patient satisfaction index was slightly higher (89.4 vs 76.3). Further, cross-sectional analysis demonstrated cost effectiveness of laparoscopic techniques and precision in complicated cases offered by robotic operations. Conclusion: The results of the present study showed that minimally invasive approaches are superior to open surgery in treating recurrent inguinal hernias in terms of postoperative recurrence, recovery, and patient satisfaction. Patient and surgery based tailored treatment planning should be vital for promoting best treatment results.